Male engagement as a strategy to improve the delivery and use of maternal, newborn, and child health services - Jean Christophe Fotso, PhD; Satyanarayan Mohanty, MSW; Ariel Higgins-Steele, MPA (Elsevier, 2015)
Background: In response to persistently poor maternal and child health in rural India, the National Rural Health Mission (NRHM) was launched in 2005 as a framework for the provision of accessible, affordable, and quality health care in deprived and underserved communities. At the centre of the programme are the accredited social health activists-local women trained as health educators and promoters to generate demand for, and facilitate access to, maternal, newborn, and child health (MNCH) services in their communities. In this study, we aimed to examine the effect of a male community health worker project on the delivery and uptake of MNCH care in a rural district of India. The specific research questions are: did male community health workers complement the work of the accredited social health activists and fill important gaps in community MNCH service delivery? Further, what is the perceived effect of male community health workers' engagement with men? Methods: We recruited and trained male community health workers, referred to as male health activists, to complement the work of the female social health activists and extend community-based delivery of MNCH services. The project was implemented between February, 2011, and March, 2013, in Keonjhar district in the state of Odisha, which is one of the six states in India with high rates of maternal and child deaths. We conducted in-depth interviews with 11 social health activists, 11 women who had recently delivered in a health facility, and seven husbands of women who had recently delivered. The interviews were conducted by locally based interviewers in the local language. Responses were audio-recorded, transcribed verbatim and translated to English, then coded manually. Findings: From the interview responses, we identified three main gender-based divisions of work and space in three areas of delivery and use of MNCH services: the escorting of women to health facilities for MNCH care; awareness raising among men on MNCH and family planning; and mobilisation of parents and children to attend village health and nutrition days and immunisation days. The narratives from virtually all respondents pointed to the crucial roles played by male health activists around and during delivery, especially at night when they facilitate transport and provide security, a role that female community health workers would rarely assume. Women and social health activist respondents were appreciative of the increased engagement of male health activists with men, which they reported resulted in some positive behaviour changes, including on family planning. Finally, the accredited social health activists identified tangible constraints, such as the cost of transport, to the implementation of village health and nutrition days and immunisation days that could only be addressed by male health activists. Interpretation: These findings highlight the potential for trained and equipped male community health workers to improve outcomes in maternal, newborn, and child health. Funding: The project and its evaluation and data analysis for this study were funded by a grant from the Bill and Melinda Gates Foundation.